Preparation method of aluminum electrode perovskite solar cell
Patent Information
- Application Number
- CN202310867408.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-15
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-07-15
AI Technical Summary
Existing perovskite solar cells without inorganic charge transport layers suffer from poor interfacial contact, numerous carrier recombination centers, low transport efficiency, and high cost of precious metal electrode materials, resulting in low device efficiency and high production costs.
A one-step method was used to prepare perovskite/TiO2 thin films as light absorption/electron transport layers on hole transport layers. Inexpensive aluminum metal thin films were used as back electrodes. TiO2 nanocrystals were synthesized by sol-gel method and introduced into the perovskite thin films using an antisolvent method, which simplifies the process steps and reduces costs.
This technology improves the photoelectric conversion efficiency of perovskite solar cells, reduces production costs, simplifies process steps, and enhances the thermal stability of devices, making it a promising candidate for commercialization.
Smart Images

Figure CN117012852B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solar cell technology and relates to a method for preparing aluminum electrode perovskite solar cells, specifically to aluminum electrode perovskite solar cells (PSCs) and their preparation method. Background Technology
[0002] With the rapid development of society and the economy, human demand for energy is constantly expanding. Finding and utilizing renewable and clean energy is of great significance for reducing fossil fuel consumption, protecting the ecological environment, and promoting sustainable social development. Solar energy, as a natural and novel energy source, allows humans to directly convert light energy into electrical energy through the photoelectric effect or photochemical reaction using solar cells, providing a new way to solve the energy crisis and possessing broad application prospects. Perovskite solar cells, due to the excellent photoelectric properties of perovskite materials, such as a wide absorption spectrum, low exciton binding energy, high mobility, and long carrier lifetime, while also possessing the advantage of low-cost fabrication through low-temperature solution processing, have become a research hotspot in the field of new energy. Currently, the photoelectric conversion efficiency (PCE) of perovskite solar cells has reached as high as 25.7%, comparable to traditional silicon solar cells, and has very promising industrialization prospects.
[0003] However, most reported high-efficiency perovskite solar cells currently utilize organic charge transport materials, which are typically synthesized at low binding energies. At higher energies, these materials often decompose, resulting in poor thermal stability at higher temperatures. Furthermore, these organic charge transport layer materials are expensive, increasing the production cost of perovskite solar cells. To address these issues, reports have indicated the use of inexpensive inorganic materials to replace organic materials as charge transport layers in perovskite solar cells, thereby improving their stability. Michael Grätzel et al. synthesized CuGaO2 nanoparticles using a hydrothermal method to prepare a hole transport layer, achieving better stability compared to perovskite solar cells based on the traditional Spiro-OMeTAD organic material (Adv. Mater. 2017, 29, 1604984). Yangyang et al. also achieved excellent stability by using ZnO nanoparticles to replace PCBM organic materials in the electron transport layer (Nat. Nanotechnol. 2016, 11, 75). However, most of the deposition based on traditional inorganic charge transport layers faces two main problems: First, poor contact at the interface between the perovskite layer and the inorganic charge transport layer introduces a large number of carrier recombination centers, which hinders charge transport and results in low device efficiency. Second, the layer-by-layer deposition process for the inorganic charge transport layer is cumbersome, and the electrode materials used in the battery devices are usually expensive precious metals such as gold and silver, which greatly increases the manufacturing cost of perovskite solar cells.
[0004] Given the various problems with current methods, it is necessary to explore a method that can improve efficiency and reduce costs for perovskite solar cells. Summary of the Invention
[0005] Technical problems to be solved To avoid the shortcomings of existing technologies, this invention proposes a method for fabricating aluminum electrode perovskite solar cells, which solves the problem that existing inorganic charge transport layer deposition methods cannot obtain high-efficiency and low-cost perovskite solar cells.
[0006] Technical solution A method for fabricating an aluminum electrode perovskite solar cell, characterized by the following steps: A hole transport layer is fabricated on a substrate; When spin-coating the perovskite precursor solution onto the hole transport layer, a chloroform solution of TiO2 is added dropwise to prepare a perovskite / TiO2 thin film as a perovskite light absorption layer / electron transport layer on the hole transport layer in a one-step method. A thin aluminum (Al) metal film is deposited on the perovskite light absorption layer / electron transport layer as the back electrode to obtain a perovskite solar cell.
[0007] The perovskite precursor solution is a MAPbI3 precursor solution and a CsMAFA ternary cation perovskite Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 )3 Precursor solution or CsPbI2Br precursor solution.
[0008] Preparation of the titanium dioxide (TiO2) nanocrystals: 2-3 mL of titanium tetrachloride (TiCl4) was added dropwise to 10-15 mL of cold anhydrous ethanol and stirred for 10-20 min; then the cooled solution was added to a round-bottom boiling flask containing 60-80 mL of anhydrous benzyl alcohol, sealed, and heated to 90-100 °C. o The solution was stirred in a constant temperature oil bath for about 6-9 hours; then ethanol was added to the obtained milky white solution to precipitate TiO2 nanocrystals.
[0009] The TiO2 chloroform solution is obtained by separating TiO2 nanocrystals precipitated in ethanol, pouring out the supernatant, and dispersing the resulting white precipitate in chloroform.
[0010] When centrifuging the TiO2 chloroform solution, centrifuge at 6000-9000 rpm for 10-15 minutes.
[0011] The concentration of TiO2 in the TiO2 chloroform solution is 40-80 mg / mL.
[0012] When preparing the perovskite / TiO2 thin film, after spin-coating the perovskite precursor solution and TiO2 chloroform solution onto the substrate, the substrate is annealed at 120-160 °C for 8-15 min.
[0013] The specific parameters for spin-coating the perovskite precursor solution are: 3000 r / min for 60 s.
[0014] The thickness of the aluminum (Al) metal thin film back electrode is 100-120 nm.
[0015] Beneficial effects This invention proposes a method for fabricating aluminum electrode perovskite solar cells. First, TiO2 nanocrystals are synthesized using the sol-gel method. Then, for the first time, TiO2 nanocrystals are introduced onto a perovskite thin film using an anti-solvent method. On one hand, Ti and O in TiO2 can bond with I and Pb in the perovskite, respectively, achieving dense interfacial contact, passivating perovskite surface defects, and suppressing non-radiative recombination and charge transport losses. On the other hand, the top TiO2 delays the evaporation of the solvent in the perovskite precursor and slows down the growth of the perovskite crystals. This allows randomly formed atomic nuclei to adjust their growth orientation with the minimum total Gibbs free energy and thermodynamically optimal direction, thereby obtaining a perovskite thin film with a larger grain size.
[0016] Advantages of this invention: This invention addresses the efficiency and cost issues of perovskite solar cells by obtaining a dense perovskite / TiO2 layer through a one-step deposition and employing an aluminum electrode. Compared to traditional layer-by-layer deposition methods of perovskite and charge transport layers, this invention first synthesizes TiO2 nanocrystals, then introduces the synthesized TiO2 nanocrystals onto the perovskite film using an anti-solvent method, followed by one-step deposition of perovskite / TiO2 through annealing, and finally uses vacuum metal evaporation technology to fabricate inexpensive aluminum as the back electrode. Test results show that the open-circuit voltage of the perovskite solar cell fabricated using this method (…) V oc ), short-circuit current density ( J sc Both the fill factor (FF) and the PCE of MAPbI3 perovskite solar cells were improved; the PCE of MAPbI3 perovskite solar cells increased from 16.2% to 19.0%; Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 The PCE of perovskite solar cells increased from 18.2% to 20.9%; the PCE of CsPbI₂Br perovskite solar cells increased from 14.4% to 17.1%; meanwhile, CsPbI₂Br devices maintained 86% of their initial efficiency after being placed at 200℃ for 200 h. This one-step deposition method reduces the process steps by half compared to the traditional layer-by-layer deposition method; at the same time, the use of aluminum electrodes in the battery devices saves 60-80% of the fabrication cost; this fabrication process and the choice of electrode materials have great commercial potential and will help to further promote the widespread application of perovskite photovoltaic devices.
[0017]
[0018] Traditional deposition methods typically involve spin-coating perovskite followed by annealing to crystallize it into a perovskite light-absorbing layer. After annealing, an electron transport layer is spin-coated onto the perovskite light-absorbing layer, followed by annealing to form the electron transport layer. One-step deposition, however, simultaneously spin-coates the electron transport material during the perovskite spin-coating process, and anneals after spin-coating to simultaneously create both the perovskite light-absorbing layer and the electron transport layer. One-step deposition simplifies the process, reduces time and equipment costs. Furthermore, the aluminum electrode deposited on the electron transport layer is significantly cheaper than silver, greatly reducing the overall cost of battery fabrication. Attached Figure Description
[0019] Figure 1 This is a structural diagram of the perovskite solar cell in this invention. Figure 2 (a) is a scanning electron microscope (SEM) cross-sectional image of the light-absorbing layer; (b) is a scanning electron microscope (SEM) cross-sectional image of the light-absorbing layer / TiO2 layer prepared by the conventional stepwise deposition method; and (c) is a scanning electron microscope (SEM) cross-sectional image of the light-absorbing layer / TiO2 layer prepared by the one-step deposition method of the present invention.
[0020] Figure 3 The image shows CsPbI2Br perovskite solar cells deposited in one step with different TiO2 concentrations under AM 1.5G solar spectral energy illumination, according to the present invention. JV Characteristic curve graph.
[0021] Figure 4 The efficiency variation of CsPbI2Br-encapsulated perovskite solar cells prepared by conventional deposition and prepared by one-step deposition at a temperature of 200 °C. Detailed Implementation
[0022] The present invention will now be further described in conjunction with the embodiments and accompanying drawings: The technical solution provided by this invention is: Preparation of titanium dioxide (TiO2) nanocrystals: Following the method reported in the literature (ACS Energy Lett. 2018, 3, 2891-2898), the specific steps are as follows: 2-3 mL of titanium tetrachloride (TiCl4) was added dropwise to 10-15 mL of cold anhydrous ethanol and stirred vigorously for 10-20 min. The cooled solution was then added to a round-bottom boiling flask containing 60-80 mL of anhydrous benzyl alcohol, sealed, and heated to 90-100 °C. o The solution was stirred in a constant-temperature oil bath at temperature C for approximately 6-9 hours. Then, ethanol was added to the resulting milky white solution to precipitate TiO2 nanocrystals.
[0023] Finally, the separation was achieved by centrifugation at 6000-9000 rpm for 10-15 min. After discarding the supernatant, the resulting white precipitate was dispersed in chloroform to prepare TiO2 chloroform solutions of different concentrations.
[0024] The above-mentioned TiO2 chloroform solution is used for one-step deposition of perovskite / TiO2 thin films.
[0025] The method for preparing the above-mentioned perovskite / TiO2 thin film is characterized by including the following steps: 1) Prepare the perovskite precursor solution; 2) Spin-coat the perovskite precursor solution prepared in step 1) onto the substrate, and add a chloroform solution of TiO2 dropwise after 25 s of spin-coating. 3) After spin coating, the substrate is annealed at 120-160 °C for 8-15 min to obtain perovskite / TiO2 thin film.
[0026] Furthermore, in step 2), the specific parameters for spin coating are: 3000 r / min 60 s.
[0027] Further, in step 2), the concentration of TiO2 in the chloroform solution of TiO2 is 40-80 mg / mL.
[0028] Further, in step 1), the perovskite precursor solution is a MAPbI3 precursor solution.
[0029] 2.1) Prepare perovskite precursor solution; 2) Spin-coat the perovskite precursor solution prepared in step 1) onto the substrate, and add a chloroform solution of TiO2 dropwise after 25 s of spin-coating. 3) After spin coating, the substrate is annealed at 120-160 °C for 8-15 min to obtain a perovskite film.
[0030] Furthermore, in step 2), the specific parameters for spin coating are: 5000 r / min 60 s.
[0031] Further, in step 2), the concentration of TiO2 in the chloroform solution of TiO2 is 40-80 mg / mL.
[0032] Further, in step 1), the perovskite precursor solution is a CsMAFA ternary cationic perovskite Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 )3. Precursor solution.
[0033] 3.1) Prepare perovskite precursor solution; 2) Spin-coat the perovskite precursor solution prepared in step 1) onto the substrate, and add a chloroform solution of TiO2 dropwise after 25 s of spin-coating. 3) After spin coating, anneal the substrate at 160-200 °C for 8-15 min to obtain a perovskite film.
[0034] Further, in step 2), the specific parameters for spin coating are: 1000 r / min, 10 s to 3000 r / min, 55 s.
[0035] Further, in step 2), the concentration of TiO2 in the chloroform solution of TiO2 is 40-80 mg / mL.
[0036] Further, in step 1), the perovskite precursor solution is a CsPbI2Br precursor solution.
[0037] A perovskite solar cell is characterized by the one-step deposition of the aforementioned TiO2 nanocrystals using an anti-solvent method to prepare a perovskite light-absorbing layer / electron transport layer. The specific structure of this cell consists of fluorine-doped tin oxide (FTO) conductive glass, a hole transport layer, a perovskite light-absorbing layer, an electron transport layer, and a back electrode stacked sequentially, as shown below. Figure 1 As shown.
[0038] The method for preparing the above-mentioned perovskite solar cells is characterized by including the following steps: S1. Pretreated substrate; S2 is used to prepare the hole transport layer; S3 one-step preparation of perovskite light-absorbing layer / electron transport layer; When spin-coating the perovskite precursor solution onto the hole transport layer, add the above TiO2 chloroform solution dropwise; Electrodes were prepared using S4 to obtain perovskite solar cells.
[0039] Taking a specific material as an example, the specific steps of the above preparation method are as follows: S1. Treatment of FTO glass: First, clean the FTO glass surface with dish soap, then ultrasonically treat it in deionized water, acetone and anhydrous ethanol containing dish soap for 10-15 minutes each, then blow it dry with nitrogen, and finally UV treat it for 15-20 minutes. S2. Spin coating of the hole transport layer: Nickel oxide (NiO) is used here. x As a hole transport material, the prepared NiO xThe solution was drop-coated onto the FTO glass treated in step S1, and spin-coated at a rate of 2000 r / min for 40 s. It was then annealed in air at 100-150 °C for 10-15 min and cooled to room temperature to obtain dense NiO. x Hole transport layer; S3. One-step deposition of perovskite light-absorbing layer / electron transport layer: ① A MAPbI3 perovskite precursor solution was prepared by adding 1.2 mol / L equimolar amounts of methyl bromide (MAI) and lead iodide (PbI2) to a mixed solvent of γ-butyrolactone and dimethyl sulfoxide (DMSO) in a volume ratio of 7:3 and stirring thoroughly. Then, this precursor solution was dropped onto NiO. x On the hole transport layer, following the procedure of 3000 r / min, 60 s, a chloroform solution of TiO2 with a concentration of 40-80 mg / mL was added dropwise when the spin coating was 40 s. The mixture was then heated at 140 ℃ for 10 min to obtain the perovskite light absorption layer / electron transport layer. ② Dissolve 1.61 mol / L formamidinium iodocarbamate (FAI), 0.052 mol / L lead bromide (PbBr2), 0.086 mol / L cesium iodide (CsI), 0.032 mol / L methyl bromide (MABr), and 2.54 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2. 60 o The FAPbI3 precursor solution was obtained by heating and stirring at C for 2 h. Then, the perovskite solution was spin-coated onto NiO. x On the hole transport layer, following the procedure of 5000 r / min for 60 s, a chloroform solution of TiO2 with a concentration of 40-80 mg / mL was added dropwise after spin coating for 40 s. Then, the perovskite film was annealed at 150°C for 15 min to obtain the perovskite light absorption layer / electron transport layer. ③ First, prepare the perovskite solution by dissolving 1 mol / L cesium iodide (CsI), 0.5 mol / L lead bromide (PbBr2), and 0.5 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2, and stirring for 2 h to obtain the CsPbI2Br precursor solution; then spin-coat the perovskite solution onto NiO. xOn the hole transport layer, the process was carried out at 2000 r / min for 10 s to 5000 r / min for 45 s. A chloroform solution of TiO2 with a concentration of 40-80 mg / mL was added dropwise 25 s during spin coating. The perovskite film was then annealed at 180 °C for 10 min to obtain the perovskite light absorption layer / electron transport layer. S4. Evaporated electrode: A 100-120 nm thick aluminum (Al) metal film is deposited on the electron transport layer as the back electrode to obtain a perovskite solar cell.
[0040] A method for obtaining high-efficiency and low-cost perovskite solar cells is characterized by the following: when spin-coating a perovskite precursor solution onto a hole transport layer, a chloroform solution of TiO2 is added dropwise, followed by annealing to obtain a perovskite / TiO2 layer; the electrode material is selected from the inexpensive metal Al.
[0041] Comparative Example 1: Compared to the examples, the comparative examples used conventional deposition methods to prepare the perovskite light-absorbing layer and electron transport layer, with the specific operations as follows: 1) Treatment of FTO glass: First, clean the surface of FTO glass with a size of 15 mm × 15 mm and an impedance of 10 Ω / sq with detergent. Then, ultrasonically treat it in deionized water, acetone and anhydrous ethanol containing detergent for 15 min each. Then dry it with nitrogen gas. Finally, UV treat the FTO glass for 15 min. 2) Spin coating of the hole transport layer: In this embodiment, NiO is used. x As a hole transport material, the prepared NiO x The solution was drop-coated onto the ITO glass treated in step 1), and spin-coated at a rate of 2000 r / min for 40 s, followed by 100 rpm in air. o Annealing at C for 10 min, followed by slow cooling to room temperature, yields dense NiO. x Hole transport layer; 3) Preparation of perovskite light-absorbing layer: ① A MAPbI3 perovskite precursor solution was prepared by adding 1.2 mol / L equimolar amounts of methyl bromide (MAI) and lead iodide (PbI2) to a mixed solvent of γ-butyrolactone and dimethyl sulfoxide (DMSO) in a volume ratio of 7:3 and stirring thoroughly. Then, this precursor solution was dropped onto NiO. x On the hole transport layer, following the procedure of 3000 r / min, 60 s, chloroform solution was added dropwise when spin coating was completed for 40 s, and the mixture was heated at 140 ℃ for 10 min to obtain the perovskite light absorption layer / electron transport layer. ② Dissolve 1.61 mol / L formamidinium iodide (FAI), 0.052 mol / L lead bromide (PbBr2), 0.086 mol / L cesium iodide (CsI), 0.032 mol / L methyl bromide (MABr), and 2.54 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2. 60 o The FAPbI3 precursor solution was obtained by heating and stirring at C for 2 h. Then, the perovskite solution was spin-coated onto NiO. x On the hole transport layer, following the procedure of 5000 r / min for 60 s, chloroform solution was added dropwise after spin coating for 40 s, and then the perovskite film was annealed at 150 °C for 15 min to obtain the perovskite light absorption layer / electron transport layer. ③ First, prepare the perovskite solution by dissolving 1 mol / L cesium iodide (CsI), 0.5 mol / L lead bromide (PbBr2), and 0.5 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2, and stirring for 2 h to obtain the CsPbI2Br precursor solution; then spin-coat the perovskite solution onto NiO. x On the hole transport layer, the process was carried out at 1000 r / min for 10 s to 5000 r / min for 45 s. Chloroform solution was added dropwise 25 s after spin coating. Then the perovskite film was annealed at 180 °C for 10 min to obtain the perovskite light absorption layer / electron transport layer. 4) Spin-coating of the electron transport layer: A 60 mg / mL TiO2 chloroform solution was spin-coated onto the perovskite film at 4000 r / min for 60 s, and then... o Anneal on the heating plate of C for 10 min; 5) Evaporated electrode: A 100 nm thick Al metal film is vapor-deposited on the barrier layer as the back electrode to obtain a perovskite solar cell.
[0042] The photoelectric performance test results of the perovskite solar cell based on MAPbI3 thin film are as follows: V oc , J sc FF and PCE were 1.056 ± 0.007 V and 21.26 ± 0.50 mA / cm, respectively. 2 0.745 ± 0.025 and 16.08 ± 0.28%.
[0043] Based on Cs 0.05 (FA0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 The photoelectric performance test results of the thin-film perovskite solar cells are as follows: V oc , J sc FF and PCE were 1.080 ± 0.008 V and 22.68 ± 0.52 mA / cm, respectively. 2 , 0.746 ± 0.021 and 17.96 ± 0.26%.
[0044] The photoelectric performance test results of the perovskite solar cell based on CsPbI2Br thin film are as follows: V oc , J sc FF and PCE were 1.179 ± 0.010 V and 15.1 ± 0.21 mA / cm, respectively. 2 , 0.769 ± 0.72 and 13.7 ± 0.34%.
[0045] Example 1: 1) Treatment of FTO glass: First, clean the surface of FTO glass with a size of 15 mm × 15 mm and an impedance of 10 Ω / sq with detergent. Then, ultrasonically treat it in deionized water, acetone and anhydrous ethanol containing detergent for 15 min each. Then dry it with nitrogen gas. Finally, UV treat the FTO glass for 15 min. 2) Spin coating of the hole transport layer: This invention uses NiO x As a hole transport material, the prepared NiO x The solution was drop-coated onto the FTO glass treated in step 1), and spin-coated at a rate of 2000 r / min for 40 s, followed by 100 rpm in air. o Annealing at C for 10 min, followed by slow cooling to room temperature, yields dense NiO. x Hole transport layer; 3) One-step deposition to prepare perovskite light-absorbing layer / electron transport layer: ① A MAPbI3 perovskite precursor solution was prepared by adding 1.2 mol / L equimolar amounts of methyl bromide (MAI) and lead iodide (PbI2) to a mixed solvent of γ-butyrolactone and dimethyl sulfoxide (DMSO) in a volume ratio of 7:3 and stirring thoroughly. Then, this precursor solution was dropped onto NiO. xOn the hole transport layer, following the procedure of 3000 r / min, 60 s, a chloroform solution of TiO2 with a concentration of 45 mg / mL was added dropwise when the spin coating was 40 s, and the mixture was heated at 140 ℃ for 10 min to obtain the perovskite light absorption layer / electron transport layer. ② Dissolve 1.61 mol / L formamidinium iodide (FAI), 0.052 mol / L lead bromide (PbBr2), 0.086 mol / L cesium iodide (CsI), 0.032 mol / L methyl bromide (MABr), and 2.54 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2. 60 o The FAPbI3 precursor solution was obtained by heating and stirring at C for 2 h. Then, the perovskite solution was spin-coated onto NiO. x On the hole transport layer, following the procedure of 5000 r / min for 60 s, a chloroform solution of TiO2 with a concentration of 45 mg / mL was added dropwise after spin coating for 40 s. Then, the perovskite film was annealed at 150 °C for 15 min to obtain the perovskite light absorption layer / electron transport layer. ③ First, prepare the perovskite solution by dissolving 1 mol / L cesium iodide (CsI), 0.5 mol / L lead bromide (PbBr2), and 0.5 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2, and stirring for 2 h to obtain the CsPbI2Br precursor solution; then spin-coat the perovskite solution onto NiO. x On the hole transport layer, the process was carried out at 1000 r / min for 10 s to 5000 r / min for 45 s. A chloroform solution of TiO2 with a concentration of 45 mg / mL was added dropwise 25 s during spin coating. The perovskite film was then annealed at 180 °C for 10 min to obtain the perovskite light absorption layer / electron transport layer. 4) Evaporated electrode: A 100 nm thick Al metal film is vapor-deposited on the electron transport layer as the back electrode to obtain a perovskite solar cell.
[0046] The photoelectric performance test results of the perovskite solar cell based on MAPbI3 thin film are as follows: V oc , J sc FF and PCE were 1.086 ± 0.007 V and 22.36 ± 0.53 mA / cm, respectively. 2 , 0.765 ± 0.021 and 18.48 ± 0.25%.
[0047] Based on Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 The photoelectric performance test results of the thin-film perovskite solar cells are as follows: V oc , J sc FF and PCE were 1.112 ± 0.007 V and 24.02 ± 0.48 mA / cm, respectively. 2 , 0.762 ± 0.025 and 20.28 ± 0.39%.
[0048] The photoelectric performance test results of the perovskite solar cell based on CsPbI2Br thin film are as follows: V oc , J sc FF and PCE were 1.225 ± 0.010 V and 15.9 ± 0.21 mA / cm, respectively. 2 0.799 ± 0.71 and 15.9 ± 0.33%.
[0049] Example 2: 1) Treatment of FTO glass: First, clean the surface of FTO glass with a size of 15 mm × 15 mm and an impedance of 10 Ω / sq with detergent. Then, ultrasonically treat it in deionized water, acetone and anhydrous ethanol containing detergent for 15 min each. Then dry it with nitrogen gas. Finally, UV treat the FTO glass for 15 min. 2) Spin coating of the hole transport layer: This invention uses NiO x As a hole transport material, the prepared NiO x The solution was drop-coated onto the ITO glass treated in step 1), and spin-coated at a rate of 2000 r / min for 40 s, followed by 100 rpm in air. o Annealing at C for 10 min, followed by slow cooling to room temperature, yields dense NiO. x Hole transport layer; 3) One-step deposition to prepare perovskite light-absorbing layer / electron transport layer: ① A MAPbI3 perovskite precursor solution was prepared by adding 1.2 mol / L equimolar amounts of methyl bromide (MAI) and lead iodide (PbI2) to a mixed solvent of γ-butyrolactone and dimethyl sulfoxide (DMSO) in a volume ratio of 7:3 and stirring thoroughly. Then, this precursor solution was dropped onto NiO. xOn the hole transport layer, following the procedure of 3000 r / min, 60 s, a chloroform solution of TiO2 with a concentration of 60 mg / mL was added dropwise when the spin coating was completed for 40 s. The mixture was then heated at 140 ℃ for 10 min to obtain the perovskite light absorption layer / electron transport layer. ② Dissolve 1.61 mol / L formamidinium iodide (FAI), 0.052 mol / L lead bromide (PbBr2), 0.086 mol / L cesium iodide (CsI), 0.032 mol / L methyl bromide (MABr), and 2.54 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2. 60 o The FAPbI3 precursor solution was obtained by heating and stirring at C for 2 h. Then, the perovskite solution was spin-coated onto NiO. x On the hole transport layer, following the procedure of 5000 r / min for 60 s, a chloroform solution of TiO2 with a concentration of 60 mg / mL was added dropwise after spin coating for 40 s. Then, the perovskite film was annealed at 150 °C for 15 min to obtain the perovskite light absorption layer / electron transport layer. ③ First, prepare the perovskite solution by dissolving 1 mol / L cesium iodide (CsI), 0.5 mol / L lead bromide (PbBr2), and 0.5 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2, and stirring for 2 h to obtain the CsPbI2Br precursor solution; then spin-coat the perovskite solution onto NiO. x On the hole transport layer, the process was carried out at 1000 r / min for 10 s to 5000 r / min for 45 s. A chloroform solution of TiO2 with a concentration of 60 mg / mL was added dropwise 25 s during spin coating. The perovskite film was then annealed at 180 °C for 10 min to obtain the perovskite light absorption layer / electron transport layer. 4) Evaporated electrode: A 100 nm thick Al metal film is vapor-deposited on the electron transport layer as the back electrode to obtain a perovskite solar cell.
[0050] The photoelectric performance test results of the perovskite solar cell based on MAPbI3 thin film are as follows: V oc , J sc FF and PCE were 1.096 ± 0.006 V and 22.76 ± 0.48 mA / cm, respectively. 2 0.785 ± 0.020 and 19.01 ± 0.20%.
[0051] Based on Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 The photoelectric performance test results of the thin-film perovskite solar cells are as follows: V oc , J sc FF and PCE were 1.124 ± 0.007 V and 24.48 ± 0.45 mA / cm, respectively. 2 , 0.792 ± 0.019 and 20.91 ± 0.21%.
[0052] The photoelectric performance test results of the perovskite solar cell based on CsPbI2Br thin film are as follows: V oc , J sc FF and PCE were 1.249 ± 0.009 V and 16.2 ± 0.1 mA / cm, respectively. 2 , 0.823 ± 0.6 and 16.7 ± 0.3%.
[0053] Example 3: 1) Treatment of FTO glass: First, clean the surface of FTO glass with a size of 15 mm × 15 mm and an impedance of 10 Ω / sq with detergent. Then, ultrasonically treat it in deionized water, acetone and anhydrous ethanol containing detergent for 15 min each. Then dry it with nitrogen gas. Finally, UV treat the FTO glass for 15 min. 2) Spin coating of the hole transport layer: This invention uses NiO x As a hole transport material, the prepared NiO x The solution was drop-coated onto the ITO glass treated in step 1), and spin-coated at a rate of 2000 r / min for 40 s, followed by 100 rpm in air. o Annealing at C for 10 min, followed by slow cooling to room temperature, yields dense NiO. x Hole transport layer; 3) One-step deposition to prepare perovskite light-absorbing layer / electron transport layer: ① A MAPbI3 perovskite precursor solution was prepared by adding 1.2 mol / L equimolar amounts of methyl bromide (MAI) and lead iodide (PbI2) to a mixed solvent of γ-butyrolactone and dimethyl sulfoxide (DMSO) in a volume ratio of 7:3 and stirring thoroughly. Then, this precursor solution was dropped onto NiO. xOn the hole transport layer, following the procedure of 3000 r / min, 60 s, a chloroform solution of TiO2 with a concentration of 75 mg / mL was added dropwise when the spin coating was 40 s, and the mixture was heated at 140 ℃ for 10 min to obtain the perovskite light absorption layer / electron transport layer. ② Dissolve 1.61 mol / L formamidinium iodide (FAI), 0.052 mol / L lead bromide (PbBr2), 0.086 mol / L cesium iodide (CsI), 0.032 mol / L methyl bromide (MABr), and 2.54 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2. 60 o The FAPbI3 precursor solution was obtained by heating and stirring at C for 2 h. Then, the perovskite solution was spin-coated onto NiO. x On the hole transport layer, following the procedure of 5000 r / min for 60 s, a chloroform solution of TiO2 with a concentration of 75 mg / mL was added dropwise after spin coating for 40 s. Then, the perovskite film was annealed at 150 °C for 15 min to obtain the perovskite light absorption layer / electron transport layer. ③ First, prepare the perovskite solution by dissolving 1 mol / L cesium iodide (CsI), 0.5 mol / L lead bromide (PbBr2), and 0.5 mol / L lead iodide (PbI2) in a mixed solvent of N,N'-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 8:2, and stirring for 2 h to obtain the CsPbI2Br precursor solution; then spin-coat the perovskite solution onto NiO. x On the hole transport layer, the process was carried out at 1000 r / min for 10 s to 5000 r / min for 45 s. A chloroform solution of TiO2 with a concentration of 75 mg / mL was added dropwise 25 s during spin coating. The perovskite film was then annealed at 180 °C for 10 min to obtain the perovskite light absorption layer / electron transport layer. 4) Evaporated electrode: A 100 nm thick Al metal film is vapor-deposited on the electron transport layer as the back electrode to obtain a perovskite solar cell.
[0054] The photoelectric performance test results of the perovskite solar cell based on MAPbI3 thin film are as follows: V oc , J sc FF and PCE were 1.089 ± 0.008 V and 22.16 ± 0.52 mA / cm, respectively. 2 , 0.775 ± 0.020 and 18.44 ± 0.24%.
[0055] Based on Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 The photoelectric performance test results of the thin-film perovskite solar cells are as follows: V oc , J sc FF and PCE were 1.117 ± 0.008 V and 23.82 ± 0.37 mA / cm, respectively. 2 , 0.771 ± 0.031 and 20.44 ± 0.32%.
[0056] The photoelectric performance test results of the perovskite solar cell based on CsPbI2Br thin film are as follows: V oc , J sc FF and PCE were 1.231 ± 0.011 V and 15.5 ± 0.23 mA / cm, respectively. 2 0.809 ± 0.74 and 15.6 ± 0.38%.
[0057] from Figure 2 As can be seen, the CsPbI2Br perovskite layer / TiO2 electron transport layer prepared by one-step deposition has better interfacial contact and the crystal size of the perovskite layer is larger.
[0058] from Figure 3 As can be seen, the CsPbI2Br perovskite solar cell fabricated based on one-step deposition, under standard light source (AM 1.5G, 100 mW / cm²), 2 Under the illumination of ), the measured JV As can be seen from the curve, it has a high photoelectric conversion efficiency.
[0059] from Figure 4 As can be seen, at a temperature of 200 °C, the CsPbI2Br device still exhibits better thermal stability after being placed for 200 h.
[0060] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the scope of the technology disclosed in the present invention, and such modifications or substitutions should all be covered within the scope of protection of the present invention.
Claims
1. A method for preparing an aluminum electrode perovskite solar cell, characterized in that... The steps are as follows: A hole transport layer is fabricated on a substrate; When spin-coating the perovskite precursor solution onto the hole transport layer, a chloroform solution of TiO2 is added dropwise to prepare a perovskite / TiO2 thin film as a perovskite light absorption layer / electron transport layer on the hole transport layer in a one-step method. The TiO2 chloroform solution was obtained by separating ethanol to precipitate TiO2 nanocrystals, pouring out the supernatant, and dispersing the resulting white precipitate in chloroform to obtain a TiO2 chloroform solution. A thin aluminum (Al) metal film is deposited on the perovskite light absorption layer / electron transport layer as the back electrode to obtain a perovskite solar cell.
2. The method for preparing an aluminum electrode perovskite solar cell according to claim 1, characterized in that: The perovskite precursor solution is a MAPbI3 precursor solution and a CsMAFA ternary cation perovskite Cs 0.05 (FA 0.98 MA 0.02 ) 0.95 Pb(I 0.98 Br 0.02 )3 Precursor solution or CsPbI2Br precursor solution.
3. The method for preparing an aluminum electrode perovskite solar cell according to claim 1, characterized in that: Preparation of the TiO2 nanocrystals: 2-3 mL of titanium tetrachloride (TiCl4) was added dropwise to 10-15 mL of cold anhydrous ethanol and stirred for 10-20 min; then the cooled solution was added to a round-bottom boiling flask containing 60-80 mL of anhydrous benzyl alcohol, sealed, and stirred in a constant temperature oil bath at 90-100℃ for 6-9 h; then ethanol was added to the obtained milky white solution to precipitate TiO2 nanocrystals.
4. The method for preparing an aluminum electrode perovskite solar cell according to claim 1, characterized in that: When centrifuging a chloroform solution of TiO2, centrifuge at 6000-9000 rpm for 10-15 min.
5. The method for preparing an aluminum electrode perovskite solar cell according to claim 1, characterized in that: The concentration of TiO2 in the chloroform solution is 40-80 mg / mL.
6. The method for preparing an aluminum electrode perovskite solar cell according to claim 1, characterized in that: In the preparation of the perovskite / TiO2 thin film, after spin-coating the perovskite precursor solution and the chloroform solution of TiO2 onto the substrate, the substrate is annealed at 120-160°C for 8-15 min.
7. The method for preparing an aluminum electrode perovskite solar cell according to claim 1, characterized in that: The specific parameters for spin-coating the perovskite precursor solution are: 3000 r / min for 60 s.
8. The method for preparing an aluminum electrode perovskite solar cell according to claim 1, characterized in that: The thickness of the aluminum (Al) metal thin film back electrode is 100-120 nm.
Citation Information
Patent Citations
Perovskite solar cell based on titanium dioxide / perovskite novel composite nano structure, and preparation method thereof
CN105428537A
Inverse perovskite solar cell device and preparation method thereof
CN114914367A
